Examining the interaction between bodily pain and mental health of construction workers. Issue 11 (1st November 2020) - Turner, Michelle; Lingard, Helen
Abstract: Construction work is physically demanding, and incidences of physical injury and work disability are high. This study explores musculoskeletal bodily pain and the impact this has on construction workers' mental health. A mixed-method approach incorporated survey and interview data. Sixty-seven construction workers completed a survey consisting of work ability and mental health measures. Eighteen workers who completed a survey participated in an interview exploring the occurrence and management of body pain, and the impact of pain on mental health. Survey findings indicated that participants whose pain had originated from work had significantly higher levels of depression, anxiety, and stress severity. Findings also revealed that depression, anxiety, and stress had a negative relationship with work ability indicators, suggesting that work ability is likely to decline when workers experience poor mental health. Key themes emerging from the interview data comprised of the expectation of pain, managing pain, impact of pain on mental health, pressure to work with pain, work ability and planning for the future, and the stigma of mental health. A conceptual model is presented which illustrates the relationship between work tasks, pain, mental health, and work ability. The model identifies that anticipated and experienced bodily pain creates harmful psychological demands for workers which impacts on their mental health.